2023
DOI: 10.1001/jamanetworkopen.2023.3630
|View full text |Cite
|
Sign up to set email alerts
|

Gender Disparity in National Institutes of Health Funding Among Surgeon-Scientists From 1995 to 2020

Abstract: ImportanceSurgical diseases account for approximately 30% of the global burden of disease. Gender diversity in biomedical research is critical to generate innovative patient-centered research in surgery.ObjectiveTo examine the distribution of biomedical research funding by the National Institutes of Health (NIH) among women and men surgeon-scientists during a 25-year period.Design, Setting, and ParticipantsThis cross-sectional study used publicly available data from the NIH RePORTER (Research Portfolio Online … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Female surgeons report significant tension between clinical and research responsibilities, and there are greater numbers of female academic surgeons on clinical tracks in their departments . In 2020, among all female academic surgeons, less than 30% receive NIH funding . In this study, we found that despite incremental increases in representation in NIH grants, female surgeons received less than 20% of NIH funding support to surgeon-scientists.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Female surgeons report significant tension between clinical and research responsibilities, and there are greater numbers of female academic surgeons on clinical tracks in their departments . In 2020, among all female academic surgeons, less than 30% receive NIH funding . In this study, we found that despite incremental increases in representation in NIH grants, female surgeons received less than 20% of NIH funding support to surgeon-scientists.…”
Section: Discussionmentioning
confidence: 54%
“…20 In 2020, among all female academic surgeons, less than 30% receive NIH funding. 21 In this study, we found that despite incremental increases in representation in NIH grants, female surgeons received less than 20% of NIH funding support to surgeon-scientists. In 2 surveys administered by the Society of University Surgeons in the past 2 decades, surgeons have called for institutions to recognize the value of surgical research and decrease the barrier to research by lowering clinical demands.…”
Section: Discussionmentioning
confidence: 64%
“…Female physicians are promoted at a slower rate, are less likely to be in leadership positions, and receive less compensation than male physicians . Uneven distribution of academic and research support, such as time and space, funding, or personnel assistance, further contributes to the problem . Furthermore, female physicians are more likely to be asked to volunteer for tasks and committees that are not relevant to or not beneficial for career advancement than their male colleagues .…”
Section: Discussionmentioning
confidence: 99%
“…A repeat analysis in 2019 noted this number had not changed that much 5 . In another study, despite receiving early career success in receiving NIH grant funding, many women surgeons remained underrepresented as surgeon-scientists pointing to other barriers during their career 48 . A recent oncology-specific analysis of 7 major hematology and oncology societies from 1994 to 2019 found women and minority groups to be underrepresented among award recipients.…”
Section: Reported Barriers and Challenges To Diversity And Inclusion ...mentioning
confidence: 99%
“…5 In another study, despite receiving early career success in receiving NIH grant funding, many women surgeons remained underrepresented as surgeon-scientists pointing to other barriers during their career. 48 A recent oncology-specific analysis of 7 major hematology and oncology societies from 1994 to 2019 found women and minority groups to be underrepresented among award recipients. Finally, it is worth noting that barriers in oncology also extend beyond what is noted above and include significant geographic and care disparities.…”
Section: Reported Barriers and Challenges To Diversity And Inclusion ...mentioning
confidence: 99%